Development of a Multilocus Sequence Typing scheme for the study of Anaplasma marginale population structure over space and time - Guillemi, Eliana Carolina; Ruybal, Paula; Lia, Veronica Viviana; Gonzalez, Sergio Alberto; Lew, Sergio Eduardo; Zimmer, Patricia Andrea; Lopez Arias, Ludmila Sol; Rodríguez, José Luis; Rodriguez, Sonia Y.; Frutos, Roger; Wilkowsky, Silvina Elizabeth; Farber, Marisa Diana (Elsevier, 2019)
Bovine Anaplasmosis caused by Anaplasma marginale is a worldwide disease prevalent in tropical and subtropical regions where Rhipicephalus microplus is considered the most significant biological vector. Molecular markers previously applied for A. marginale typing are efficient for isolate discrimination but they are not a suitable tool for studying population structure and dynamics. Here we report the development of an MLST scheme based on the study of seven genes: dnaA, ftsZ, groEl, lipA, recA, secY and sucB. Five annotated genomes (Saint Maries, Florida, Mississippi, Puerto Rico and Virginia) and 53 bovine blood samples from different world regions were analyzed. High nucleotide diversity and a large proportion of synonymous substitutions, indicative of negative selection resulted from DnaSP 5.00.02 package application. Recombination events were detected in almost all genes, this evidence together with the coexistence of more than one A. marginale strain in the same sample might suggest the superinfection phenomena as a potential source of variation. The allelic profile analysis performed through GoeBURST shown two main CC that did not support geography. In addition, the AMOVA test confirmed the occurrence of at least two main genetically divergent groups. The composition of the emergent groups reflected the impact of both historical and environmental traits on A. marginale population structure. Finally, a web-based platform “Galaxy MLST-Pipeline” was developed to automate DNA sequence editing and data analysis that together with the Data Base are freely available to users. The A. marginale MLST scheme developed here is a valuable tool with a high discrimination power, besides PCR based strategies are still the better choice for epidemiological intracellular pathogens studies. Finally, the allelic profile describe herein would contribute to uncover the mechanisms in how intracellular pathogens challenge virulence paradigm.